Compositional profile of barley landlines grown in different regions of Gilgit‐Baltistan. Issue 5 (24th March 2021) - Hussain, Abid; Ali, Sartaj; Hussain, Azhar; Hussain, Zubair; Manzoor, Muhammad Faisal; Hussain, Abid; Ali, Amjad; Mahmood, Talat; Abbasi, Kashif Sarfraz; Karrar, Emad; Hussain, Maqsood; , Tajudin
Abstract: The current investigation was performed to explore the nutritional and functional composition of four landlines of barley denoted as LB1 (Gilgit), LB2 (Nagar), LB3 (Skardu), and LB4 (Shigar) from different regions of Gilgit‐Baltistan. The samples were examined for nutritional profile and antioxidant attributes. Total phenolic values and total flavonoid results were in the range of 1.2 to 3.1 mg/g and 0.41 to 0.55 mg/g, respectively. Nutritional profile as crude starch, fiber, protein, ash, and fat ranged from 56.3%–50.80%, 16.50%–11.73%, 16.20%–11.53%, 2.8%–2.1%, and 2.63%–1.63%, respectively. The mineral composition in terms of Mg (527–616 mg/kg) was higher in the landlines followed by Ca (312–368 mg/kg), Na (122.6–146.6 mg/kg), Fe (43.3–65.6 mg/kg), and Zn (22.5–26.6 mg/kg). It was concluded that the indigenous barley landlines had immense nutritional potential and functional attributes. Thus, it can be used for value‐added food products and the development of cottage industry in the region. Abstract : The current study demonstrated that the local barley landline is a good source of nutrition as well as functional properties with good antioxidant activity. Thus, it is suggested that the crop should be an essential part of our diet and also used for making value‐added products. The current study further provides baseline data for future research in the food and pharmaceutical aspects of barley landlines.